Clinical and immunological associations in myasthenia gravis. 2. Cell-mediated immunity. - Sagar, H J (1980)
Myasthenic patients showed low absolute T cell counts and low spontaneous and phytohaemagglutinin-induced lymphocyte transformation responses. The abnormalities were particularly associated with late onset disease and female sex, but not with HLA phenotype or autoantibody production. Serum factors inhibitory to lymphocyte transformation occurred in some patients.